The Influence of Arabic Culture on European Medieval Romance & Poetry - قاسم, فطيمة حسين (Revues faculté des lettres et des langues, 2018)
Abstract: The present study traces the Arabic influences on the literary development of medieval poetry and romance (originally verse narratives of love and chivalry). It aims to highlight areas of such contributions in some of the greatest European Medieval Romances ( E.M.R) and poetry, and link them to their counterparts in Arabic Literary Tradition (A.L.T). It provides an analytical review of Menocal’s book and some of the related arguments by western scholars, who support the Arabist theory, and confess the west indebtedness to Arabic culture. Conclusively Translation was the initiative media for such peculiar cultural and literary interchange. It played a tremendous role in the awakening of Medieval Europe, and its later upheaval الملخص تهدف هذ الدراسة إلى تتبع تأثير الثقافة العربية في الأدب الأوروبي خلال العصور الوسطى وتحديدا في الشعر والأدب الروومانثي(قصص الفروسية والحب الشعرية). وتعتمد الدراسة في مجملها على بحوث وشهادات الكتاب الغربيين المنصفين خاصة الباحثة الأمريكية من أصول أسبانية ماريا روزا مينوكال التي تصدت لدحض إدعاءات الدراسات النقدية التي تنكر هذا التأثير.  وتتضح أهم ملامح هذا التأثير في شعر التروبادور الذي اشتق اسمه من كلمة "طرب" وتعود أصوله إلى موشحات الحب الأندلسية. وكذلك تأثر قصص الرومانث بالتقليد الشعري العربي للحب العذري. وتحفل هذه الدراسة بالكثير من الأمثلة والمقارنات التي توضح هذا التأثير. وتخلص الدراسة إلى أهمية الترجمة وتعلم لغة " الآخر"  في المثاقفة والتفاعل بين الحضارات. وهذا ما انتشل أوروبا من ظلام العصور الوسطى إلى عصر النهضة أو الرينيسانس.